Pengaruh Kuat Arus Dan Kecepatan Pengelasan Smaw Sistem Sliding Adaptive Two Axis Terhadap Hasil Pengelasan Baja Karbon Rendah - Putra, Ivan Fadillah; Yohanes, Yohanes; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Low carbon steel can be welded with all types of welds. One of the welding techniques is SMAW (Shielded Metal Arc Welding), which has its own advantages, under which the large current can be varied as the heat source used, easy to use in different welding positions and penetration and width of melting electrodes can be adjusted. This study uses an SMAW welding machine with a sliding adaptive two-axis system that varies the current strength and welding speed according to the characteristics of the weld, by visual observation, tensile strength and microstructure on the weld. The parameters were varied from the strength of the 90 A, 100 A and 120 A currents and the welding speed controlled by the Arduino Uno with the rotation of the stepper motor as a driver. The material used a low-carbon steel, using V camp with a vertical angle of 600. The results of the study show that the highest tensile strength of 505.31 Mpa and the lowest value of 224.20 Mpa. The micro-weld structure was determined by many factors, including heat input, current, welding speed and cooling speed. In this study, the HAZ area has a larger grain structure than the base metal and the weld metal.keywords Current, Welding Speed, SMAW, Sliding Adaptive Two.